Synthesis and Evaluation of Bone Targeting PLGA Nanoparticles Loaded with Components of Traditional Chinese Medicine Formulas - Zhao, Zehao; Deng, Yanling; Deng, Yu; Chen, Zhuojun; Zhou, Zhikun (Recent Patents on Nanotechnology, 2024)
Background: Targeted nanoparticles' preparation can enhance local drug concentration and reduce the side effects of drugs in non-targeted organs. At present, many patents have been applied for in the field of bone-targeted nanoparticles' preparations. They play an important role in the treatment and diagnosis of diseases. In this experiment, nanoparticles with bone targeting function were prepared by poly(lactic-co-glycolic acid) (PLGA) copolymer and tetracycline. These nanoparticles contain active ingredients in the Huangqi Sanxian decoction, a kind of Traditional Chinese Medicine (TCM) compound formula. These nanoparticles are predicted to be useful in the treatment of osteoporosis.Methods: Synthesis of tetracycline targeting groups was performed by acylation reaction, and PLGA nanoparticles were prepared by the Emulsification-solvent Evaporation Method. The appearance and particle size of the product were evaluated, and the effects of nanoparticles on the physiological activities of osteoblasts were observed. Finally, the bone-targeting ability of targeted nanoparticles in vivo and in vitro was investigated.Results: The average particle size of the nanoparticles was about 200 nm, and the average drug entrapment was 60%. In vitro evaluation of osteoblasts assay showed that the nanoparticles can be well taken by cells. Their good biocompatibility and sustained-release properties reduce the toxic side effects of drugs when they promote osteoblasts' physiological activities. The results of the in vitro and in vivo bone targeting ability assays showed that tetracycline modified nanoparticles could effectively accumulate in the bone, indicating the great bone-targeting ability of the nanoparticles. The use of PLGA to load active components in the TCM compound formulas and remodel targeting groups is expected to improve drug efficacy, reduce drug dosage, and effects on non- action sites. This may provide new ideas for the development of TCM compound dosage forms.Conclusion: In summary, we prepared PLGA nanoparticles of multiple TCM ingredients with bone targeting ability, and they had good morphological appearance, and a promoting effect on various physiological activities of osteoblasts.
Keywords: osteoblasts